2009
DOI: 10.1103/physrevb.79.024103
|View full text |Cite
|
Sign up to set email alerts
|

Post-spinel transformations and equation of state inZnGa2O4: Determination at high pressure byin situx-ray diffraction

Abstract: Room temperature angle-dispersive x-ray diffraction measurements on spinel

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
32
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 36 publications
8
32
2
Order By: Relevance
“…No evidence of phase transition is found up to 13 GPa. Even the tetragonal distortion of the cubic spinel structure, observed in other spinels under compression, 9 is not observed in our experiments. This fact contradicts the conclusions extracted from resistivity measurements.…”
Section: A Sample Characterizationcontrasting
confidence: 43%
See 2 more Smart Citations
“…No evidence of phase transition is found up to 13 GPa. Even the tetragonal distortion of the cubic spinel structure, observed in other spinels under compression, 9 is not observed in our experiments. This fact contradicts the conclusions extracted from resistivity measurements.…”
Section: A Sample Characterizationcontrasting
confidence: 43%
“…11 This fact is in contradiction with the results reported for spinel ZnGa 2 O 4 for which the compression of the cubic and tetragonal polymorphs can be described with the same equation of state (EOS). 9 On top of that, HP resistivity experiments carried out in CoFe 2 O 4 nanocrystals indicated that the phase transition to the post-spinel structure occurs at 7.5 and 12 GPa for 80 and 6 nm particles, respectively. 12 The reduction of the transition pressure from 20 GPa to less than 12 GPa was explained as a consequence of the transformation of CoFe 2 O 4 into a metastable phase that does not exist in the bulk material.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among other techniques, they have been studied by XRD, being several pressure-induced transitions reported. [6][7][8][9][10][11][12][13][14][15] The reversibility of these transitions is subject of dispute. In some cases, it has been found that the transitions are not reversible, being metastable polymorphs recovered at ambient conditions after decompression.…”
Section: Introductionmentioning
confidence: 99%
“…To check if we can recover this transition from our theory, we carried out calculations within GGA+U+SO at different pressures. At this point, we would like to mention that certain cubic spinels such as ZnGa 2 O 4 [21] are observed to undergo cubic to tetragonal structural transition under pressure. Since no experimental information is available in literature about the distortions introduced by application of pressure on cubic spinel CoV 2 O 4 , it is worth exploring the possibility of a cubic to tetragonal transition in this system on increasing the pressure.…”
Section: Gga+u+so: Transport Properties Under Pressurementioning
confidence: 99%